Stability of Proton Superoxide and its Superionic Transition Under High Pressure - Zifan Wang; Wenge Yang; Duck Young Kim (Advanced Science, 2025)
Abstract Under extreme conditions, condensed matters are subject to undergo a phase transition and there have been many attempts to find another form of hydroxide stabilized over H2O. Here, using Density Functional Theory (DFT)‐based crystal structure prediction including zero‐point energy, it is that proton superoxide (HO2), the lightest superoxide, can be stabilized energetically at high pressure and temperature conditions. HO2 is metallic at high pressure, which originates from the 𝜋* orbitals overlap between adjacent superoxide anions (O2−). By lowering pressure, it undergoes a metal‐to‐insulator transition similar to LiO2. Ab initio molecular dynamics (AIMD) calculations reveal that HO2 becomes superionic with high electrical conductivity. The possibility of creating hydrogen‐mixed superoxide at lower pressure using a (Lix,H1‐x)O2 hypothetical structure is also proposed. This discovery bridges gaps in superoxide and superionicity, guiding the design of various H‐O compounds under high pressure.